(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The research to find out: "1) the emotional intelligence of the grade X students of MAS Al Manaar Pulu King of the school year 2017/2018. 2) The student learning results on the exponent and logarithmic material of the grade X student MAS Al Manaar Pulu of the King’s school year 2017/2018. 3) Influence of students ’ emotional intelligence with student learning outcomes on exponent and logarithmic material in grade X students of MAS Al Manaar Pulu King of the school year 2017/2018. This research is an investigational study with a type of experimental quasi research. The population is a student of X Mas Al Manaar Pulu Raja, with a sample number of 32 students. Data analysis is recognized with qualitative data analysis and descriptive data analysis. The findings show: 1. Average emotional intelligence of grade X student MAS Al Manaar Pulu King is 63.84, or includes high catagories with the highest score of 76 and the lowest value of 37. 2. On average, the student mathematics of the grade X MAS Al Manaar pulp is on the material exponent and logarithm of 56.25, or the category is enough with the highest value of 95 and the lowest value of 35. 3. There is a positive and significant influence between the emotional intelligence to the outcome of students ’ mathematics learning on the exponent and logarithmic material of class X MAS Al Manaar Pulu Raja with > This which is 2.492 > 1.996. Where the student’s emotional intelligence is influential against the students ’ math learning results of 63.84 with a high catagory with an average study result of 56.25 with enough catagories. Thus there is an influence between students ’ emotional intelligence toward student learning outcomes.